Study guides

Q: Subtract 9x-9 from 2x plus 3?

Write your answer...

Submit

Related questions

2x + 3 = x + 1 Subtract x from both sides: x + 3 = 1 Subtract 3 from both sides: x = -2

3x + 4 = 2x - 3 Subtract 2x from both sides: x + 4 = - 3 Subtract 4 from both sides: x = -7

x + 3 + 2x = x + 3 subtract x + 3 to both sides 2x = 0 divide by 2 to both sides x = 0

3x+8 = 2x+5 Subtract 2x from both sides: x+8 = 5 Subtract 8 from both sides: x = -3

6X + 3 = 2X + 19Subtract 3 from each side:6X = 2X +16Subtract 2X:4X = 16Divide by 4X = 4

2x plus y = -3 (subtract 2x from both sides) y = -2x - 3 slope = -2 y-intercept = -3

4x + 2 = 2x + 5 Subtract through by 2x 2x + 2 = 5 Subtract through by 2 2x = 3 Divide through by 2 x = 1.5 ■

Do you do all your homework on answers.com? 2x + 3 =9 subtract 3 from each side 2x = 6 divide each side by 2 x = 3

2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!

First you subtract 3x from both sides and get -7=2x+3. Then subtract 3 from both sides and get -10=2x. Then divide both sides by 2 and x=-5.

If it is 3x2 + 4 = 2x + 4, then you can subtract 4 from both sides, and get 3x2 = 2x, and then x = 2/3

2x + 3 = 9x Subtract 2x from each side: 3 = 7x Divide each side by 7: x = 3/7.

First, let's put that information into an equation. 2x + 3 = 6 + 4xSubtract 2x from both sides.3 = 6 + 2xSubtract 6 from both sides.-3 = 2xDivide each side by 2.x = -3/2

7x + 13 = 2x + 3 First, subtract 3 from both sides.7x + 13 - 3 = 2x + 3 - 3Simplify both sides.7x + 10 = 2xNow, subtract 2x from both sides.7x - 2x + 10 = 2x - 2xSimplify again.5x + 10 = 0Finally, subtract 10 from both sides, simplify, and divide both sides by 5.5x + 10 - 10 = 0 - 105x = -10x = -2So the answer is x = -2.

2x + 3 = 9x Subtract 2x from both sides: 3 = 7x Divide both sides by 7: 3/7 = x

2x + 6 = 9 (subtract 6 from both sides) 2x = 3 (divide both sides by two)x = 1.5

4x plus 3 plus 2x is equivalent to expression 6x plus 3.

2x + 3 + 23x = 25x +3

(2x + 3)(x + 1 ) = 2x^2 +5x +3

4x-39 = 2x+3, 4x-2x = 42 x=21

2x + 3=7x

Subtract x from each side: 5 = x - 3 so x = 8

4x-3=2x+9 (original problem) 2x-3=9 (subtract 2x from both sides) 2x=12 (add 3 to both sides) x=6 (divide both sides by 2)

2x + 2 = x + 5Subtract 2 from each side:2x = x + 3Subtract 'x' from each side:x = 3

1)add 5 to each side ,2x+8=4x 2)subtract 2x from each side, 8=2x 3) divide each side by 2, x=4